Publicidade digital : apropriações e implicações na atuação publicitária de profissionais de Belém do Pará no contexto da midiatização profunda - SOUSA, Thatianne Silva (Universidade Federal do Pará, 2025)
This work focuses on digital advertising in the context of deep mediatization and takes as its empirical object the opinion of advertising professionals in Belém do Pará. Thus, the guiding questions of the research are: how are the modes of production and circulation of digital advertising in the context of deep mediatization, which occur globally, appropriated in local contexts, and what are the implications for the advertising practices of professionals in Belém do Pará?. This is a qualitative research, with a methodology inspired by cartography and we used bibliographical survey, documentary research, and fieldwork as methods, applying the technique of semistructured personal interviews. The fieldwork was conducted in three stages, namely: field I, interviews with advertising researchers, to understand the theme of transformations in advertising within the digital environment; fields II and III, interviews with advertising professionals, to identify perceptions of digital advertising and its implications for their practices. The theoretical frameworks employed to dialogue with the field interviews included deep mediatization and datafication; mediatization in the Amazon; digital advertising flow; transformations in the advertising field and work; and advertising education and ethics. As results, based on interviews with advertising professionals, we identified that: they understand the transformations in the production and circulation of advertising in the digital environment but face limitations regarding regulation and platform rules, and, at times, how to act when faced with ethical dilemmas imposed by the market; advertising in Belém do Pará faces challenges unique to the region, requiring a balance between local relevance and global transformations; and, as the main finding, the relationships between academic training, advertising ethics, and the particularities of the local context, which are essential pillars for understanding and practicing advertising in the digital environment. Finally, we understand that advancing toward relevant advertising, education, and ethical practices requires a constant (re)thinking of advertising practices, always considering the perspectives of local identities and regional appreciation.